Carbon nanotubes as gene carriers: Focus on internalization pathways related to functionalization and properties. (February 2017) - Caoduro, Cécile; Hervouet, Eric; Girard-Thernier, Corine; Gharbi, Tijani; Boulahdour, Hatem; Delage-Mourroux, Régis; Pudlo, Marc
Graphical abstract: Abstract: Carbon nanotubes represent promising transporters for delivery of DNA and other biomolecules into living cells. Various methods of CNTs surface functionalization have been developed. These are essential to improve CNTs dispersibility and permit their interactions with biological structures that broaden their use in advanced biomedical applications. The present review discusses the different single walled carbon nanotubes and multiwalled carbon nanotubes functionalization methods, leading to the formation of optimized and functionalized-CNT complexes with DNA. F-CNTs are recognized as efficient and promising gene carriers. Emphasis is then placed on the processes used by f-CNTs/DNA complexes to cross cell membranes. Energy independent pathways and uptake mechanisms dependent on energy, such as endocytosis or phagocytosis, are reported by many studies, and if these mechanisms seem contradictory at first sight, a detailed review of the literature illustrates that they are rather complementary. Preferential use of one or the other depends on the DNA and CNTs chemical nature and physical parameters, experimental procedures and cell types. Statement of Significance: Efficient non-viral gene delivery is desirable, yet challenging. CNTs appear as a promising solution to penetrate into cells and successfully deliver DNA. Moreover, the field of use of CNTs as gene carrier is large and is currently growing. This critical review summarizes the development and evaluation of CNTs as intracellular gene delivery system and provides an overview of functionalized CNTs/DNA cellular uptake mechanisms, depending on several parameters of CNTs/DNA complexes.